Economic value and clinical association of a supervised lifestyle-improving program for MASLD - Polignano, Maurizio; Bianco, Antonella; Guido, Davide; Trisolini, Pietro; Franco, Isabella; Bonfiglio, Caterina; Giannelli, Gianluigi (Frontiers in Pharmacology, 2026)
BackgroundMetabolic dysfunction-associated steatotic liver disease (MASLD) is both common and, in some cases, a progressive condition. Emerging pharmacological options have shown promise in select patient sub-groups (e.g., resmetirom for MASH with fibrosis; GLP-1 receptor agonists for obesity/diabetes with metabolic benefits), but structured lifestyle programs remain foundational in routine care.ObjectiveThis study evaluates the cost–utility analysis of a multidisciplinary, kinesiology-supervised lifestyle-improving program for patients with MASLD, supported by clinical evidence.MethodsWe analyzed 27 adults with MASLD, a cohort established from an initial group of 43 subjects, who participated in a structured program of supervised exercise and dietary counseling. Health-related quality of life (SF-36 mapped to EQ-5D) and associated clinical markers, including hepatic steatosis (ultrasound), blood pressure, and serum aminotransferases, were evaluated at baseline and after the program. A cost–utility analysis was conducted from the healthcare system’s perspective, estimating the incremental cost-effectiveness ratios (ICERs and €/QALY) with deterministic and probabilistic sensitivity analyses. Pharmaceutical expenditures and projected disease progression costs were also explored using administrative data and literature-based models.ResultsHealth-related quality of life improved after the program, with a quality-adjusted life year (QALY) gain of 0.081 (95% CI: 0.001–0.161). The base-case ICER was €17,778/QALY. The probability of cost-effectiveness was 71% at €25,000/QALY, 84% at €30,000/QALY, and 95% at €40,000/QALY. Ultrasound steatosis showed a distributional shift toward lower grades with an unchanged median (Wilcoxon p = 0.007). Systolic/diastolic blood pressure decreased by −5.6/−3.7 mmHg (p = 0.05 and p = 0.03), and AST/ALT declined (both p < 0.01). At the 2-year follow-up, 55.6% of patients reported maintaining regular physical activity. Outpatient pharmaceutical expenditures showed a decline from €74 to €50 per patient/year between 2018 and 2021, with reduced variability across patients. However, this trend did not reach statistical significance in mixed-effects analyses (p = 0.06).ConclusionIn this pre–post observational study, the supervised program was associated with favorable cost–utility outcomes and distributional improvements in selected clinical markers. These findings support the program’s potential value in routine care and warrant confirmation in controlled studies.Clinical Trial Registrationhttps://clinicaltrials.gov/expert-search?term, identifier NCT06026293.